Identification of phytochemicals from borreria alata (aubl.) Dc. Using lc-ms-qtof (Bangladesh Journal of Botany, 2025)
The present investigation determined the phytochemical components of Borreria alata through the utilisation of LC-MS. A total of 88 phytochemicals were identified with a retention time ranging from 1 to 21 minutes. Ten phenolic compounds, two flavonoids, six amines and six amino acids were identified among them. The results of this study showed the medicinal and allelopathic potential of B. alata.Bangladesh J. Bot. 54(3): 425-431, 2025 (September)